Pengembangan media pop-up dan monopoli interaktif sebagai sarana pembelajaran sejarah islam di mts - Maghfiroh, Novita Lailatul; Salwa, Ainatus (Maliki Interdisciplinary Journal, 2025)
Learning media is an important component in supporting the success of the teaching and learning process, especially in increasing students' motivation and understanding of material that is considered difficult or less interesting. In the context of learning Islamic history, especially material about Walisongo, innovative strategies and media are needed so that students can understand the material more easily and enjoyably. One form of learning media innovation is pop-up media and monopoly educational games. Pop-up media presents a visualization of important figures, events, and places in Walisongo's history in an attractive and easy-to-understand three-dimensional form. Meanwhile, monopoly media is designed as an educational game that contains questions, challenges, and information about Walisongo's da'wah struggle in the archipelago. This paper examines the development and application of pop-up and monopoly media based on local wisdom in the learning of Islamic history at the Madrasah Tsanawiyah level. This study uses a qualitative descriptive method with a limited literature study and field trial approach. The purpose of this study is to provide alternative learning media that is able to increase students' interest, active involvement, and understanding of Walisongo history material. It is hoped that the results of this study can encourage educators to be more creative in conveying Islamic history material with a contextual, fun, and in accordance with the characteristics of 21st century students.